Response of Leucaena leucocephala to inoculation in a soil of pH 5.5 - Almeida, J.E.; Valarini, Maria José; Lopes, Eli Sidney (International Center for Tropical Agriculture, 1982)
A glasshouse experiment compared the performance of strains of Rhizobium with Leucaena leucocephala in a "cerrado" soil limed to pH 5.5. Liming increased dry matter production, but variation within replicates was so great that increases in nodule dry weight and N2 fixed were not statistically significant.